Die Medienöffentlichkeit der Rechtsprechung und ihre Grenzen - Jahn, Jannika (2021)
The study analyses how the opposing legal interests can be balanced in the reporting on judicial proceedings and case law as well as in the opinions expressed by judges in the media, and to what extent a communicative approach to judicial public relations can complement the balance achieved within the framework of the regulatory approach. In doing so, constitutional theory and, for a better understanding of the potential effects on the media, above all communication science findings will be used. The relevant case law of the European Court of Human Rights is taken into account as well as current legal developments in England and France.